2018
DOI: 10.1177/1535370218813988
|View full text |Cite
|
Sign up to set email alerts
|

Trientine selectively delivers copper to the heart and suppresses pressure overload-induced cardiac hypertrophy in rats

Abstract: Dietary copper supplementation reverses pressure overload-induced cardiac hypertrophy by copper replenishment in the heart. A copper-selective chelator, trientine (triethylenetetramine [TETA]), reverses left ventricular hypertrophy associated with diabetes also by copper replenishment in the heart. The present study was undertaken to address the critical issue how TETA delivers copper to the heart. Adult male Sprague-Dawley rats were subjected to transverse aortic constriction (TAC) to induce cardiac hypertrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…Therefore, Cu exserts a potent cardiovascular health relevance because of its incorporation as a cofactor in antioxidant superoxide dismutase, lysyl oxidase, and mitochondrial cytochrome c-oxidase (Fukai et al 2018). Studies revealed that Cu de ciency (CuD) could be a leading cause of adverse cardiac events including ischemic and hypertrophic disorders (DiNicolantonio et al 2018, Li et al 2018, Liu et al 2018. Also, the alteration in the myocardial Cu acquisition mechanism was recently pointed out as the key factor in diabetes-induced heart failure in rats (Zhang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Cu exserts a potent cardiovascular health relevance because of its incorporation as a cofactor in antioxidant superoxide dismutase, lysyl oxidase, and mitochondrial cytochrome c-oxidase (Fukai et al 2018). Studies revealed that Cu de ciency (CuD) could be a leading cause of adverse cardiac events including ischemic and hypertrophic disorders (DiNicolantonio et al 2018, Li et al 2018, Liu et al 2018. Also, the alteration in the myocardial Cu acquisition mechanism was recently pointed out as the key factor in diabetes-induced heart failure in rats (Zhang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…86 However, a recent study showed that TETA at a lower dosage (21.9 mg/kg day) actually selectively delivered copper to the copper-deficient hypertrophic hearts in rats. 21 Further studies revealed the possible mechanism by which TETA facilitates copper accumulation selectively in cardiomyocytes through the formation of Cu(II)-TETA complex that is transported to cardiomyocytes via an energy-dependent, but CTR1-independent, cross membrane transportation process in cardiomyocytes. 87…”
Section: Copper Induced Myocardial Angiogenesismentioning
confidence: 99%
“…In the process of copper-induced angiogenesis, the fibrotic scar is also ameliorated, due to an increase of MMP-2 protein level and activity in the heart. 21 The coordination between angiogenesis and destruction of fibrotic scar guarantees a suitable microenvironment for myocardial regeneration.…”
Section: Angiogenesis In Myocardial Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that cardiac hypertrophy caused by pressure overload can be promoted by supplementing copper to promote the regression of cardiac hypertrophy [195][196][197]. However, for patients with diabetes and DCM, copper deficiency in cardiomyocytes is not due to insufficient dietary intake, but the inability of excess copper ions in blood to enter cells.…”
Section: Interventions For Cuproptosis Associated With Dcmmentioning
confidence: 99%